2020
DOI: 10.3389/fmicb.2020.00693
|View full text |Cite
|
Sign up to set email alerts
|

Recto-Anal Junction (RAJ) and Fecal Microbiomes of Cattle Experimentally Challenged With Escherichia coli O157:H7

Abstract: Cattle are the asymptomatic reservoirs of Escherichia coli O157:H7 (O157) that preferentially colonizes the bovine recto-anal junction (RAJ). Understanding the influence of O157 on the diversity of the RAJ microbiota could give insights into its persistence at the RAJ in cattle. Hence, we compared changes in bovine RAJ and fecal microbiota following O157 challenge under experimental conditions. Cattle were either orally challenged (n = 4) with10 10 CFU of a streptomycin-resistant O157 strain 86-24, or mock-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 45 publications
2
11
0
2
Order By: Relevance
“… 77 , likely due to individual and environment particularities. Of note, despite high dose infective inoculum (10 10 CFU), the abundance of the Escherichia-Shigella taxon did not increase in challenged calves; a phenomenon that was previously reported 77 , 78 .…”
Section: Discussionsupporting
confidence: 64%
“… 77 , likely due to individual and environment particularities. Of note, despite high dose infective inoculum (10 10 CFU), the abundance of the Escherichia-Shigella taxon did not increase in challenged calves; a phenomenon that was previously reported 77 , 78 .…”
Section: Discussionsupporting
confidence: 64%
“…Higher alpha diversity identified among some STEC shedders has been observed in previous studies in both beef [16,54] and dairy cattle [22]. By contrast, some reports have found that STEC carriage in individual cattle was associated with lower alpha diversity [17,20,23,55].…”
Section: Discussionsupporting
confidence: 51%
“…Zhao et al (2013), for instance, found that butyrate-producing species were more abundant in low-STECshedding cattle and were critical in avoiding RAJ lesions [17], suggesting the role of certain taxa as "inhibitors" or "promoters" [17]. Contrasting results have been observed among studies, but in general, there is a consensus that STEC shedders have a higher proportion of members from the order Clostridiales, the dominant order found in the bovine gut microbiome [18,[21][22][23][24]54,55,57]. Consistent with other reports, a lower abundance of Proteobacteria was observed in STEC shedders [22,55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations